Proučevanje vzpetin kopastega krasa s pomočjo digitalnega modela višin - Stefanovski, Sašo (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2019)
The main goal of the article is detection and classification of cone karst landforms in four different study areas in Slovenia and the introduction of new Dinaric cone karst findings based on the morphometric analysis. Analysis was made in ArcMap 10.4.1, where the landforms were recognized using the Fill tool. Authors found out that cone karst is a very diverse type of relief that differs from area to area. The biggest factors of cone karst landform shaping are structural geological settings and the depth of the vadose zone.
Keywords: digital elevation model; digitalni model višin; Dinaric karst; Dinarski kras; fizična geografija; geografski informacijski sistemi; geomorfologija; geomorphology; GIS; physical geography; Slovenia; Slovenija